Nadja y la experiencia del azar: una propuesta literaria-filosófica del surrealismo desde el pragmatismo de william james (2020)
This thesis presents a literary and existential-philosophical analysis of surrealism, based on André Breton's work Nadja. For this, it looks for parallelisms between surrealism and William James' pragmatism. This way, a literary work is read with philosophical eyes, which allows a fluent proposal about an expansive world that allows itself to be affected by azar as this azar is allowed to be part of everydayness. Finally, this thesis seeks to anchor these proposals to the present world. This is why it analyzes the covid-19 pandemics, and proposes a surrealistic way of live to deal with it.